Clímaco soto Borda y Diana cazadora : una carcajada en la literatura colombiana (2005)
ABSTRACT: The main concern of this article is to identify the literary context for Clímaco Soto Borda´s novelDiana cazadora (1915). The author points out how intertextuality permeates the novel, a fact that relates it to many other important contemporary novels, even European ones. Another aspect addressed here is the ironical humour used by Soto Borda which places his work as an avant-garde proposal for Colombian literature at that period.